2005
DOI: 10.1021/ja052184t
|View full text |Cite
|
Sign up to set email alerts
|

QZ1 and QZ2:  Rapid, Reversible Quinoline-Derivatized Fluoresceins for Sensing Biological Zn(II)

Abstract: QZ1, 2-[2-chloro-6-hydroxy-3-oxo-5-(quinolin-8-ylaminomethyl)-3H-xanthen-9-yl]benzoic acid, and QZ2, 2-[6-hydroxy-3-oxo-4,5-bis-(quinolin-8-ylaminomethyl)-3H-xanthen-9-yl]benzoic acid, two fluorescein-based dyes derivatized with 8-aminoquinoline, have been prepared and their photophysical, thermodynamic, and zinc-binding kinetic properties determined. Because of their low background fluorescence and highly emissive Zn(II) complexes, QZ1 and QZ2 have a large dynamic range, with 42-and 150-fold fluorescence enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
190
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 251 publications
(197 citation statements)
references
References 105 publications
7
190
0
Order By: Relevance
“…In these systems, the 1:1 Zn 2+ -ligand complex was too spectroscopically similar to the metal-free probe to allow observation by a simple fluorimetric titration. The K d values for the 2:1 Zn 2+ -ligand complexes of ZAP4 (23 μM) and 6-CO 2 H-ZAP4 (22 μM) are similar in magnitude to those measured for the QZ family (18).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In these systems, the 1:1 Zn 2+ -ligand complex was too spectroscopically similar to the metal-free probe to allow observation by a simple fluorimetric titration. The K d values for the 2:1 Zn 2+ -ligand complexes of ZAP4 (23 μM) and 6-CO 2 H-ZAP4 (22 μM) are similar in magnitude to those measured for the QZ family (18).…”
Section: Discussionsupporting
confidence: 67%
“…The equilibrium constant measured from the forward and backward rates agrees well with that obtained from singular value decomposition analysis of the titrations. The rate constant associated with the dissociation is greater than those measured for ZP1 probes, but less than those measured for QZ probes, as is the rate of Zn 2+ release (18).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It has been reported that some zinc(II) probes such as ZS5 and QZ1 respond to exogenously added zinc(II) more quickly in neurons than in other normal cell types, such as HeLa and COS-7. 23 Less than 1 min of incubation was sufficient to observe full fluorescence enhancement in hippocampal neurons following treatment with 50 mM zinc(II)/pyrithione, whereas 5 min was required to observe complete turn-on in HeLa cells. 24 Therefore, we questioned whether FluoZin-3AM would respond to intracellular zinc(II) on a faster time scale, a feature that is necessary for monitoring biological zinc(II) flux, in normal cell type.…”
Section: Imaging Endogenous Zinc(ii) Mobilizationmentioning
confidence: 95%
“…23,27,33,34 Symmetrical sensors tend to have lower extinction coefficients than their asymmetrical counterparts, thereby lowering fluorescence emission in the metal-free state and increasing the effective dynamic range. 23,25 One of the symmetrical probes illustrated in Fig. 1, QZ2, 25 displays particularly interesting sensing characteristics by comparison to the first generation Zinpyr (or ZP) family of probes.…”
Section: Introductionmentioning
confidence: 99%